Numerical simulation of effect of operating conditions on flash reduction behaviour of magnetite under H2 atmosphere. (8th October 2019) - Wang, Xingnan; Fu, Guiqin; Li, Wei; Zhu, Miaoyong
Abstract: The flash reduction behaviour of in-flight magnetite particles under hydrogen atmosphere is investigated by an Eulerian-Lagrangian model to explore the effect of operating conditions. In addition to quantitatively analysing the variations of the reduction degree and residence time of particles at the reactor exit, the reduction state of particles moving in the reactor is depicted by time evolutions of particle temperature, reduction rate, and reduction degree. Results show that the heating time of particles is too short to affect the reduction process. Higher temperature, H2 partial pressure, and operating pressure are conducive to the flash reduction because of a higher reaction rate. Although water vapour promotes the heat transfer inside the reactor, it weakens the reduction rate. Increasing particle feeding rate has a negative effect, with the effect becoming more significant as total gas flow declines. This study can provide a theoretical basis for flash ironmaking technology in hydrogen atmosphere. Graphical abstract: The effects of operating conditions on the flash reduction behavior of in-flight magnetite particles in H2 atmosphere were investigated using a 3D Eulerian−Lagrangian model. The results provide both theoretical and technical basis for the flash ironmaking technology. Image 1 Highlights: CFD modeling of flash reduction behaviour of magnetite particles in H2 . Effects of operating conditions on reduction degree and particle residence time. Evolution of reduction state of magnetite particles moving in the reactor. Increasing water vapour promotes heat transfer but weakens reduction rate.